Berberine Ameliorates Glucose Metabolism in Diabetic Rats through the alpha7 Nicotinic Acetylcholine Receptor-Related Cholinergic Anti-Inflammatory Pathway - Wang, Dingkun; Ren, Yanlin; Sun, Wei; Gong, Jing; Zou, Xin; Dong, Hui; Xu, Lijun; Wang, Kaifu; Lu, Fuer (Planta Medica, 2021)
Berberine is an isoquinoline derivative alkaloid extracted from Chinese herbs. Recent studies have demonstrated the therapeutic effect of berberine on glucose metabolic disorders. However, its specific mechanism is still unclear. Our study aimed to research the glucose-lowering effect of berberine in diabetic rats and to reveal the possible role of the cholinergic anti-inflammatory pathway. Diabetic rats induced by administration of a high-calorie diet and streptozocin tail vein injection were assessed by the oral glucose tolerance test. Then, the diabetic rats were divided into two groups, those with or without the alpha7 nicotinic acetylcholine receptor gene downregulated, respectively, followed by treatment including berberine for 6 weeks. Results of this study show that the administration of berberine downregulated levels of fasting blood glucose and fasting insulin, and ameliorated insulin resistance in diabetic rats. Treatment with berberine inhibited acetylcholinesterase activity, and upregulated acetylcholine levels in the serum and alpha7 nicotinic acetylcholine receptor gene expression in the liver tissue. Meanwhile, berberine reversed elevated expression of cytokines interleukin-1β and TNF-α in the serum and downregulated nuclear factor κB expression. However, berberine administration showed no glucose-lowering or anti-inflammatory effect in diabetic rats in which alpha7 nicotinic acetylcholine receptor gene expression was downregulated, and acetylcholinesterase activity was also significantly inhibited. In conclusion, berberine may ameliorate glucose metabolism by activating the alpha7 nicotinic acetylcholine receptor-mediated cholinergic anti-inflammatory pathway.
Keywords: berberine; glucose metabolism; α7nAchR; cholinergic anti-inflammatory pathway; Ranunculaceae; Berberidaceae; Rutaceae